Students - Sari, Yunita; Miftah, M. Zaini; Qamariah, Zaitun (Institut Agama ISlam Negeri Palangka Raya, 2021)
This study was designed to know students‟ perception toward english teacher pedagogical competence. The survey design was applied in this study. The research subjects were the eleventh-grade students in senior high school. In Government Regulation No.74 2008 there are four competencies that the teacher should have. The focus of this research is on teacher‟s pedagogical competence. In National Education Standards Agency pedagogical competence is teacher‟s ability in understanding the students, designing and implementing the learning, evaluating the learning outcome and also the development of the potentials that the student have. This study used questionnaire to collect the data from the students. The researcher distributed the questionnaire to the students in google form via WhatsApp. The findings showed that the students have a possitive perception toward English teacher pedagogical competence which contained (1) understanding students; (2) designing and implementing learning; (3) evaluating learning outcomes; (4) development of learners to actualize the potential they have. The English teacher pedagogical competence categorized sufficient competence which 57% (Neutral).